The first year: the support needs of parents caring for a child with an intellectual disability. (19th July 2016) - Douglas, Tracy; Redley, Bernice; Ottmann, Goetz
Abstract: Aim: To describe the support needs of parents caring for a child with an intellectual disability in the first year of life. Background: Parents of children with intellectual disabilities face significant challenges during the first year of their child's life which is an important developmental period not previously addressed in the literature. The provision of support by health professionals, particularly nurses and midwives, during this crucial period can impact on parental well‐being and on the health and developmental outcomes of their children. However, parents often feel unsupported. Design: The study used a qualitative descriptive methodology. Methods: Semi‐structured interviews were conducted with parents of eleven children with an intellectual disability in Victoria, Australia, during 2014. Interviews were digitally recorded, transcribed verbatim and analysed using thematic data analysis. Findings: Three key areas of support need were identified to assist parents to provide effective care for their child with an intellectual disability in the first year of life: (1) emotional support as parents adjusted to their role of caring for a child with an intellectual disability; (2) information support as they embarked on a quest for knowledge; and (3) support to facilitate their connection to peer networks. The findings highlighted inconsistent provision of support for parents. Conclusion: This study informs health professionals about how to provide holistic, timely support to parents of children with intellectual disabilities in the first year of life. There is an urgent need to review how nurses and midwives can provide relevant support that is responsive to parents' needs.